International Tribunals Approach Toward Maritime Boundaries Delimitation of an Archipelagic State - Nurbintoro, Gulardi (UI Scholars Hub, 2024)
One of the most prominent features of the United Nations Convention on the Law of the Sea (UNCLOS) is the recognition of the archipelagic State concept, embodied under Part IV of the Convention. Since the entry into force of the Convention, more than 20 countries have claimed archipelagic State status, all of which are developing countries. Despite the considerable number of archipelagic States and a universal recognition of the concept, judicial jurisprudence remains very limited, if not non-existent, with respect to practices of archipelagic States pertaining to maritime boundaries delimitation. Up to the writing of this abstract, only two maritime boundary delimitation cases involving an archipelagic State were presented before an adjudication tribunal, namely the 2006 Barbados/Trinidad and Tobago Arbitration and the 2023 Mauritius/Maldives Delimitation of the Maritime Boundary in the Indian Ocean. This paper aims to review and analyze, in spite of the limited jurisprudence, how tribunals interpret and apply the provisions of maritime boundary delimitation to an archipelagic State. Mindful of such limitations, this paper does not aim to provide a conclusive review of today’s state of archipelagic State concept. It views the limited jurisprudence as evidence that issues pertaining to maritime boundary delimitation of an archipelagic State are largely unexplored and require further sanctioning through State practices and through judicial decisions.